Comparing the Effectiveness of Evidence-Based Parenting Programs on Families of children with and without Special Educational Needs: Short-term and Long-term Gains - Totsika, Vasiliki; Mandair, Sashvinder; Lindsay, Geoff (Frontiers in Education, 2017)
Parents of children with a disability or special educational needs (SEN) have three available options when accessing parenting programmes: (a) to access a parenting programme that has been adapted for use by families with a child with disability, (b) to access a disability-specific parenting programme, or (c) to access a parenting programme developed for typically developing children. The aim of the present study was to examine whether accessing evidence-based parenting programmes (EBPPs) developed for typically developed children (option c) could benefit families of children with SEN, and whether benefits could be maintained when programme delivery takes place as part of sustained service implementation. Using data from an effectiveness trial, we found that there was no evidence of differential effectiveness: i.e., families of children with SEN experienced similar gains to families whose child did not have SEN with respect to child behaviour problems, parenting style and parental mental well-being. Using data from services’ sustained implementation, our findings indicated that gains during the implementation phase were of similar magnitude to gains during the research trial: following EBPPs, families of children with SEN experienced small to moderate improvements in behaviour problems and moderate to large improvements in parenting and parental mental well-being across the two phases. One year later, gains were significantly maintained in families who had accessed EBPPs as part of the research trial. While the study is not proposing that EBPPs developed for typically developing children are a replacement for disability-adapted or disability-specific parenting programmes, there was a pragmatic need to evaluate the effectiveness of EBPPs that are in practice accessed by families with a child with SEN. Overall, families of children with SEN can benefit from EBPPs similarly to families whose child does not have SEN, and the gains are significant and substantial even when EBPPs are offered as part of regular service provision. Longer-term maintenance of gains (one year) in service-led implementation of EBPPs likely requires more input.